GC-MS-based metabolomics of volatile organic compounds in exhaled breath: applications in health and disease. A review - Bajo-Fernández, María; Souza-Silva, Érica A.; Barbas, Coral; Rey-Stolle, Ma Fernanda; García, Antonia (Frontiers in Molecular Biosciences, 2024)
Exhaled breath analysis, with particular emphasis on volatile organic compounds, represents a growing area of clinical research due to its obvious advantages over other diagnostic tests. Numerous pathologies have been extensively investigated for the identification of specific biomarkers in exhalates through metabolomics. However, the transference of breath tests to clinics remains limited, mainly due to a deficiency in methodological standardization. Critical steps include the selection of breath sample types, collection devices, and enrichment techniques. GC-MS is the reference analytical technique for the analysis of volatile organic compounds in exhalates, especially during biomarker discovery phase in metabolomics. This review comprehensively examines and compares metabolomic studies focusing on cancer, lung diseases and infectious diseases. In addition to delving into the experimental designs reported, it also provides a critical discussion of methodological aspects, ranging from the experimental design and sample collection to the identification of potential pathology-specific biomarkers.